1980
DOI: 10.1128/jb.143.2.703-709.1980
|View full text |Cite
|
Sign up to set email alerts
|

tif-Stimulated deoxyribonucleic acid repair in Escherichia coli K-12

Abstract: Bacterial survival is significantly increased after ultraviolet irradiation in tif sfi cells, provided that the thermosensitive tif mutation has been expressed at 410C before irradiation. This tif-mediated "reactivation of ultraviolet irradiated bacteria" needs de novo protein synthesis, as is the case for the tif-mediated reactivation of ultraviolet-irradiated phage A. However, in striking contrast to the phage reactivation process, this tif-mediated reactivation is no longer associated with mutagenesis. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our results demonstrate that the DNA damage-inducible SOS response plays a role in upregulating NER capacity in E. coli. The existence of such an upregulation after DNA damage has been previously postulated for several reasons, including (i) the demonstration that uvrA, uvrB, and uvrD were under Rec/Lex control and were induced rapidly after DNA damage (1,18,24,38); (ii) the dramatic increase in phage (5,48) and bacterial (5,12) survival if cells were preinduced by low flu- ences of UV or by genetic means; (iii) the reduced rate of CPD repair in recA mutants and the subsequent rapid rate of CPD repair when the SOS response was derepressed in the same cells (12); and (iv) the decrease in cell survival when protein synthesis treatments were given immediately following UV (13,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that the DNA damage-inducible SOS response plays a role in upregulating NER capacity in E. coli. The existence of such an upregulation after DNA damage has been previously postulated for several reasons, including (i) the demonstration that uvrA, uvrB, and uvrD were under Rec/Lex control and were induced rapidly after DNA damage (1,18,24,38); (ii) the dramatic increase in phage (5,48) and bacterial (5,12) survival if cells were preinduced by low flu- ences of UV or by genetic means; (iii) the reduced rate of CPD repair in recA mutants and the subsequent rapid rate of CPD repair when the SOS response was derepressed in the same cells (12); and (iv) the decrease in cell survival when protein synthesis treatments were given immediately following UV (13,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the relevance of SOS-dependent protein induction to NER have produced conflicting results. Castellazzi et al (5) showed that recA441 mutants, grown at 41°C to induce the SOS response, had an enhanced UV survival compared to an isogenic recA ϩ strain under the same conditions. The enhanced survival depended on de novo protein synthesis and the presence of wild-type uvrA.…”
mentioning
confidence: 99%
“…It has also been reported that the lethal filamentation caused by low UV doses in an ruv-9 strain is not suppressed by the sfiAll mutation (20 (8). The sfiAll and sfiB103 mutations were further shown not to diminish tifor UV-induced reactivation of UV-inactivated A phage, and the sfiAll mutation does not affect tif-induced mutagenesis of A (5,8). Similarly, as shown in Fig.…”
mentioning
confidence: 93%